MARKETING RESEARCH OF THE INFLUENCE OF PRICE POLICY ON CONSUMER BEHAVIOR (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract Introduction. Economic terms "marketing pricing policy" are considered in the article, "behavior of consumers", interpretation different foreign and home scientists, it is given their description. The role of marketing pricing policy is investigational for companies and consumers of products or services. It is considered types of consumer behavior and their reaction on a price.The purpose of the article. Research of approaches in relation to determination of concept "marketing pricing policy" their value and terms of pricing, consideration of term "behavior of consumers", research of types of behavior of consumers and their reaction on a price.Methods. During research the methods of comparison, analysis, synthesis, abstraction, theoretical, historical and logical generalization are used. The dialectical method of research became methodological basis.Results. It is exposed essence of economic term "marketing pricing policy" and "behavior of consumers". The conducted research showed that a competent price policy is an important component of the company's marketing strategy, because the price is one of the key factors taken into account by consumers when making purchase decisions. The study of consumer behavior is a priority area in the activity of any company, because consumers, after purchasing goods, bring profit to it. Therefore, for the successful operation of the company, customers must be in the center of attention. By studying consumers, their motives, wishes, price categories, and purchase processes, companies try to offer buyers exactly what they need.Conclusiоns. A study of theoretical and practical aspects of the marketing policy of pricing and consumer behavior was conducted, the types of consumer behavior and their reaction to the price were investigated. It was determined that the influence of marketing price policy on consumers is a key factor in making a purchase decision. Price politics determines the cost of commodities and services, that influences on perception of general utility of product consumers. The question of the factors that influence the behavior of consumers that most encourage the purchase of goods or services requires further research. Defining the role and place of price in making a purchase.
Keywords: marketing, price, pricing policy, consumer behavior, marketing price policy.